Analysis of Dream Paradigm in Islamic Perspective - Aida Hayani; Wani Maulida; Aisyah Rahmawati; Ahmad Zulfikar Habibullah (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
Dreams are mental phenomena that occur during sleep. Precognitive dreams are one type of dream, where the dream becomes a reality in the future. This dream is often experienced by certain people such as prophets, saints and others. The purpose of this article will be to discuss how to dream from an Islamic point of view. The method in this article is library research, to know the validity of data, the researcher use content analasis data, to analyze data in this research use are  reduction data, classification and verification. The results of the study show: First, the presence or absence of God's contribution that causes the sacredness of dreams. Second, the comparison above looks at the images that appear when dreaming. Third, the difference in terms of the axiology of dreams. Fourth, the ethics of dream interpretation or interpretation. All humans experience dreams that are identical to sleeping flowers or in the form of images that do not make sense, but dreams actually show the quality of one's spirit or soul. The better and clearer a person's soul, the more meaningful the truth of his dream. Therefore, it is necessary for humans and Muslims in particular, to always improve themselves both in external and spiritual practices, in order to be able to get quality dreams and contain the truth.